Eco Gender Gap in Animated Films: Real and Fictional Gender-based Differences in Environmental Sensitivity - Dalila Forni (Pensa MultiMedia, 2022)
Animated films are nowadays an important and popular narrative medium that can create a socially shared imaginary. For this reason, they are considered an important indirect educational tool. One of the many applications of animation at pedagogical level is in environmental awareness, an area recently intertwined with Gender Studies. Research agrees on the existence of a marked gender gap in ecological interest (eco gender gap): data indicate that women usually approach environmental issues more effectively than men. Comparing social facts to imaginative figures proposed by narratives, similar trends emerge: if in real life ecological commitment is mainly female, also in film narratives it is mainly female characters who show a greater interest and sensitivity towards the environment. The study therefore intends to analyze some classic animated films, from Disney products to Studio Ghibli's movies, in order to understand how the ecological issue is intertwined with gender, identifying the most relevant characters and their approach towards contact and respect for nature. The research wants to explore a parallelism between social and imaginary perception of nature and the environment, so as to open a reflection on how gender might be a determining element in the approach to ecology on different levels.